PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA DISTRIK NAVIGASI KELAS II SEMARANG - Yohanes Caesarido Satrio Nugroho, 10.05.51.0147 (Students Journal of Economic and Management, 2016)
This study aims to examine and analysis the effect of motivation and job satisfaction on staff performance on Distrik Navigasi Kelas II Semarang. The research instrument used in this study qualify validity, with factor analysis. Because all of the indicators in the research instrument has Loading factors or matrix components above 0.4; thus also the value of Kaiser meyer Olkin measure of sampling adequacy (KMO) or condition is above 0.5. Reliability testing of the variables studied has proven its reliability or consistency, because it has a Cronbach alpha greater than 0.6. Model studies have shown the value of the coefficient of determination (Adjusted R2) of 0.667 that qualifies the goodness of fit or the model is able to explain the variables studied. The results showed positive and significant effect of motivation on staff performance with regression coefficient 0.408, significance level of 0.000, and 7.641 t value. Job satisfaction showed a positive and significant effect on staff performance with regression coefficient 0.174, significance level of 0.000, and 4.357 t value. Key words : motivation, job satisfaction, staff performance